The Mathematical Literacy Task Using the Context of the Traditional Games “Engklek” and “Congklak” - Caswita; Nurain Suryadinata; Siti Mutmainah (Riemann: Research of Mathematics and Mathematics Education, 2026)
The low level of mathematical literacy among Indonesian students remains a significant challenge, as evidenced by PISA and national assessment results. Although ethnomathematics has been widely recognized as a promising approach to contextualize mathematics learning, studies that specifically develop mathematical literacy tasks based on traditional games and examine their validity, practicality, and effectiveness are still limited. In particular, the integration of traditional games such as "Engklek" and "Congklak" into mathematical literacy task design has not been extensively explored. This study aims to develop mathematical literacy tasks using the context of the traditional games "Engklek" and "Congklak" that meet the criteria of validity, practicality, and effectiveness. Employing a design research methodology with a development study approach, this study adopted a formative evaluation model consisting of self-evaluation, expert review, one-to-one, small-group, and field test stages The subjects were junior high school students in Bandar Lampung. Data were collected through walkthroughs, documentation, observations, interviews, and tests, then analyzed using descriptive qualitative methods. The results show that the developed tasks achieved a high level of validity based on expert judgment, with consistent agreement across content, construct, and language aspects. The tasks were also found to be practical, as indicated by students’ positive responses and their ability to engage with the tasks during trials. Furthermore, the field test revealed an improvement in students’ mathematical literacy performance, particularly in formulating, employing, and interpreting mathematical problems within real-life contexts. Therefore, it can be concluded that the ethnomathematics-based mathematical literacy tasks developed in this study are valid, practical, and effective, and suitable for supporting students’ development of mathematical literacy.